Decomposing the gap in intimate partner violence between Scheduled Caste and General category women in India: An analysis of NFHS-5 data - Sourav Chowdhury; Aditya Singh; Nuruzzaman Kasemi; Mahashweta Chakrabarty (Elsevier, 2022)
Scheduled Caste (SC) women, one of India's most oppressed and neglected population groups, are the most vulnerable to intimate partner violence (IPV). IPV, on the other hand, is less common among women in the General category. No study has been conducted to measure the gap in IPV between these two groups. This study is an attempt to fill this gap. This study aims to comprehensively explore the factors that underlie and explain the gap in IPV between SC and General women. Information on 10,168 ever-married SC and 9695 ever-married General women aged 15-49 from the fifth round of the National Family Health Survey was analyzed. The Fairlie decomposition (Blinder-Oaxaca decomposition modified for binary outcomes) was used in this study to explain the gap in ever experience of IPV prevalence between SC and General women. About 37.3% and 24.4% of ever-married SC and General women in India suffered either physical or mental or sexual violence from their husbands. The large part of the gap in IPV between SC and General women was due to differences in husbands' alcohol consumption (26.33% gap), wealth index (24.48% gap), controlling behavior by husband (24%) and parental IPV (15.87% gap). With the introduction of appropriate interventions and programs, these gaps can be reduced. Interventions aimed at reducing alcoholism should be emphasized.